2023
DOI: 10.3390/life13040927
|View full text |Cite
|
Sign up to set email alerts
|

Humic Substances as a Feed Supplement and the Benefits of Produced Chicken Meat

Abstract: Humic substances with a high proportion of humic acids (more than 40%) have been classified by the European Commission as feed materials that can be used in animal nutrition since 2013. A protective effect on the intestinal mucosa, as well as anti-inflammatory, adsorptive and antimicrobial properties, were recorded. Nutrient absorption, nutritional status and the immune response in chickens supplemented with HSs were significantly improved. HSs have the ability to enhance protein digestion as well as the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…A final mode of action of how HV could improve animal resiliency in the face of stressors could involve oxidative stress. Marcinčák et al (2023) observed that an added humic substance improved the oxidative stability of meat during storage, especially meat with higher fat content. Work from Dyomshyna et al (2023) reported that adding a humic substance to the water of gerbils increased the activity of catalase, an antioxidant enzyme, and decreased malonic dialdehyde, a prooxidant in liver mitochondria.…”
Section: Discussionmentioning
confidence: 97%
“…A final mode of action of how HV could improve animal resiliency in the face of stressors could involve oxidative stress. Marcinčák et al (2023) observed that an added humic substance improved the oxidative stability of meat during storage, especially meat with higher fat content. Work from Dyomshyna et al (2023) reported that adding a humic substance to the water of gerbils increased the activity of catalase, an antioxidant enzyme, and decreased malonic dialdehyde, a prooxidant in liver mitochondria.…”
Section: Discussionmentioning
confidence: 97%
“…For many reasons, humic substances (HS) attract the increased attention of scientists. Depending on the region of occurrence, heterogeneous macromolecular structures and compositions of HS may change (Marcinčák et al, 2023). Because of their disparate origins and natures, as well as the fact that their bio-effects vary depending on specification, it is therefore challenging to compare the real effects of HS preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Feed additives are currently successfully and widely applied in animal nutrition. The biological and chemical breakdown of plant biomass by microbes results in the formation of humic substances (HS), which are naturally occurring organic bioactive compounds present in soil (Marcinčák et al, 2023). These organic residues, which contain humic and fulvic acids, are made up of decomposing organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…12 Thus, animal feed safety is an important cornerstone of food safety. 13 Fish meal is used as an addition to animal feed, owing to its balanced amino acid composition, high calcium and phosphorus contents, and rich nutrition. 14,15 The improper processing and storage of fish meal results in the microbial fermentation of proteins and high levels of biogenic amines.…”
Section: Introductionmentioning
confidence: 99%